1992
DOI: 10.1128/mcb.12.12.5499
|View full text |Cite
|
Sign up to set email alerts
|

Unstable amplification of two extrachromosomal elements in alpha-difluoromethylornithine-resistant Leishmania donovani.

Abstract: We describe the first example of unstable gene amplification consisting of linear extrachromosomal DNAs in drug-resistant eukaryotic cells. cx-Difluoromethylornithine (DFMO)-resistant Leishmania donovani with an amplified ornithine decarboxylase (ODC) gene copy number contained two new extrachromosomal DNAs, both present in 10 to 20 copies. One of these was a 140-kb linear DNA (ODC140-L) on which all of the amplified copies of the odc gene were located. The second was a 70-kb circular DNA (ODC70-C) containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 60 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…Amplicons in Leishmania spp. can be found either as extrachromosomal circles (reviewed in references 2, 27, and 41) or as linear molecules with telomeric sequences (14,15,25,34,47). Circular and linear amplicons contain either direct (head-to-tail) or inverted (head-to-head) repeats (3,16,19,23,29,34,43), two types of structures also found in extrachromosomal circular amplicons of tumor cells (reviewed in references 39 and 40).…”
mentioning
confidence: 99%
“…Amplicons in Leishmania spp. can be found either as extrachromosomal circles (reviewed in references 2, 27, and 41) or as linear molecules with telomeric sequences (14,15,25,34,47). Circular and linear amplicons contain either direct (head-to-tail) or inverted (head-to-head) repeats (3,16,19,23,29,34,43), two types of structures also found in extrachromosomal circular amplicons of tumor cells (reviewed in references 39 and 40).…”
mentioning
confidence: 99%
“…It targets ornithine decarboxylase (ODC) (17), an enzyme involved in the production of trypanothione, which is essential for redox homeostasis in trypanosomes (18). It is known that overexpression of ODC can yield resistance in Leishmania donovani (19), and we showed that, in trypanosomes, it clearly confers a selective advantage to cells growing under DFMO pressure (Fig. 2).…”
mentioning
confidence: 76%
“…These amplicons appear to be linear in nature by their pulse time-dependent migration on contourclamped homogeneous electric field gels (46). Leishmania species exhibit considerable chromosomal plasticity in response to stress and are known to amplify both circular and linear chromosomal elements in response to selective pressure (32,33,(47)(48)(49)(50). Although the L. donovani genome has not been reported, the genome of L. infantum, a species phylogenetically akin to L. donovani, reveals that APRT is localized ϳ29 kb from the end of chromosome 26 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Pulse Field Gel Electrophoresis (PFGE)-InCert-agarose (Cambrex, Rockland, ME) plugs (5%) containing 2 ϫ 10 7 L. donovani promastigotes were prepared as described (32,33). Chromosomes of wild type, ⌬aprt, ⌬hgprt/⌬xprt, and two independent clones of ⌬hgprt/⌬xprt[Ino/Hyp] parasites were fractionated by PFGE using a contour-clamped homogeneous electric field gel apparatus (Bio-Rad) on a 1% agarose gel at 14°C for 24 h with a 60-s pulse time in 0.5ϫ Tris-borate-EDTA buffer as described (33).…”
Section: Expression Of Aprt In Escherichia Coli-mentioning
confidence: 99%
See 1 more Smart Citation